THERMOCHEMICAL DATA ON MINERAL PHASES: THE SYSTEM CAO-MGO-AL2O3-SIO2 - Saxena Surendra K.; Chatterjee Nilanjan (My University, 1986)
Thermochemical data on several phases forming in the system CaO-MgO-Al2O3-SiO2 have been tested for consistency in reproducing experimental phase equilibrium relationships. Calorimetric data on enthalpy, entropy and heat capacity have been adjusted within experimental errors and new data on some phases have been estimated using phase equilibrium data. The consistency of the data in reproducing phase equilibrium relations in the multicomponent-multiphase systems has been tested by computing phase diagrams using the method of minimization of total Gibbs free energy. The recent calorimetric data on most phases can be used without any significant change except for phases that show cation disorder. Disorder corrections have been added to the heat capacity data on gehlenite, anorthite, spinel and Ca-Tschermak.